To the 100th anniversary of M. G. Zeldovich’s birt - Шеховцова, Тетяна Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
To the 100th anniversary of M. G. Zeldovich’s birth